Can we do the right thing?: subtitling African American vernacular English into French - Mevel, Pierre-Alexis (2012)
Situated at the intersection of Translation Studies, Sociolinguistics and Film Studies, this thesis provides an analysis of the subtitling into French of a corpus of films portraying speakers of African American Vernacular English (henceforth AAVE). By analysing the French subtitles, the thesis focuses on the possibility of using non-standard forms in the target language, on their potential impact on the reception of a film, and on the theoretical underpinnings of juxtaposing two linguistic varieties on screen.